Media power and hegemony in South Africa : the myth of independence - Ngwenya, Blessed, 1980- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book critically explores how meanings of 'independence' are constructed and reconfigured by public service broadcasters in the global south, with a particular focus on the South African Broadcasting Corporation (SABC). Responding to the ideological trappings wrought by modernity and coloniality, which continue to influence the way broadcasters and media in the global south operate, Blessed Ngwenya questions traditional institutional, political-economy and world systems paradigms, and presents a radical local understanding of freedom in the present day. The author draws on an empirical study of 36 in-depth interviews with members of staff from the SABC, including board members, senior management, and journalists, offering an intimate insight into how the participants themselves perceive, understand, and deal with the issues and problems they face in relation to independence. Framed by a rich analysis of the historical events necessitating such investigations, this book provides readers with the theoretical and empirical toolkit needed to place the everyday worlds and needs of their subjects first, and to ultimately arrive at an accurate understanding of independence in its several senses. Contributing to growing global debates on the decolonisation of knowledge, this book is critical reading for advanced scholars and researchers of African media, culture, communication and epistemic freedom"--
Introduction: Thought, Word and Deed -- Foundations of Public Service Broadcasting (PSB) in South Africa -- The Early Transition of the SABC From State Broadcaster to Post-Apartheid Broadcaster: Global Designs Local Histories -- Citizen and Consumer -- The ANC and the Hazards of Neo-Liberal Midwifery: Implications for SABC Independence -- Controversies and Challenges to Contemporary Broadcasting: A Possible Epistemic Dis-Obedience? -- SABC 'Independence' Conceptions and Dilemmas of Universality: Whither SABC?
OCLC-licensed vendor bibliographic record.
Keywords: South African Broadcasting Corporation; Public broadcasting -- South Africa; Mass media policy -- South Africa; HISTORY / Africa / South / South Africa; POLITICAL SCIENCE / Political Freedom & Security / General